2017
DOI: 10.1155/2017/8085462
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Capacity of Dental Pulp Stem Cell Regulated by SDF-1α-CXCR4 Axis

Abstract: Previously, the perivascular characteristics of dental pulp stem cells (DPSCs) were reported, which suggested the potential application of DPSCs as perivascular cell source. In this study, we investigated whether DPSCs had angiogenic capacity by coinjection with human umbilical vein endothelial cells (HUVECs) in vivo; in addition, we determined the role of stromal cell-derived factor 1-α (SDF-1α) and C-X-C chemokine receptor type 4 (CXCR4) axis in the mutual interaction between DPSCs and HUVECs. Primarily isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
(61 reference statements)
5
21
0
Order By: Relevance
“…Moreover, co-cultures demonstrate that DPCs participate in the formation of more stable blood vessels by promoting endothelial cells proliferation and migration covering HUVECs, acting as pericytes [92]. According to our results, besides expressing mesenchymal stem cell markers, primary isolated hDPCs were also positive for perivascular markers, namely a-SMA, suggestive of their perivascular origin, as reported in previous studies [92,93]. In this sense, the incorporation of hDPCs in this novel injectable system might enhance the revascularization and new tissue ingrowth.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, co-cultures demonstrate that DPCs participate in the formation of more stable blood vessels by promoting endothelial cells proliferation and migration covering HUVECs, acting as pericytes [92]. According to our results, besides expressing mesenchymal stem cell markers, primary isolated hDPCs were also positive for perivascular markers, namely a-SMA, suggestive of their perivascular origin, as reported in previous studies [92,93]. In this sense, the incorporation of hDPCs in this novel injectable system might enhance the revascularization and new tissue ingrowth.…”
Section: Discussionsupporting
confidence: 89%
“…This is indicated that the tissue regeneration process by DPSC on the 7th day had not occurred well. This is supported by previous research that that on the 7th day of the HDPSC injection post there were no significant results on the microvascular structure, which is one of the important factors in the regeneration process [24]. showed that there was a significant increase in Alpha-Amylase-1 markers (AMY-1) marker of differentiation of acinar cells and FGF7 which are mesenchymal markers.…”
Section: Discussionsupporting
confidence: 78%
“…Both the formation and function of new blood vessels are improved by either injection of DPSCs into neuronal disease models or transplantation of DPSCs into ischemia and myocardial infarction animal models [ 101 , 102 ]. Moreover, Nam et al observed that by coinjection of DPSCs and HUVECs into immunodeficient mice, microvessel-like structures would be formed, which illustrated that DPSCs could perform as perivascular cells for in vivo angiogenesis [ 103 ]. DPSCs also have the ability to differentiate into endothelial-like cells.…”
Section: Dental Pulp Stem Cells (Dpscs)mentioning
confidence: 99%